Description of business processes of the sales activities of an industrial enterprise - O. V. Martynova; R. M. Akhmetshin (Путеводитель предпринимателя)
At the present stage of economic development, the problem of increasing the efficiency of enterprise management is becoming more urgent. In the scientific literature, effective management is considered through the construction of business processes. The sales system or sales activities is one of the key links of the organization; accordingly, its effective construction ensures the achievement of planned indicators for the competitive development of the enterprise. The article describes the business processes of the sales activities of an industrial enterprise, the analysis of which makes it possible to identify problems and improve efficiency. In the process approach, the description of the main processes is based on the actions that need to be performed to achieve the result. Process–oriented management allows you to qualitatively change the activities of an organization at the operational, cross–functional and inter–organizational levels. In the article, the description of business processes is focused on the sales activities of the enterprise, the effective organization of which determines the financial results of the organization. The article discusses the processes of planning and sales of finished products, warehousing and storage of finished products, development and approval of packaging for finished products, contains their description and provides performance indicators of the built processes. The effectiveness of a business process is proposed to be assessed by various indicators and ranges of their values, which depend on the process itself.